Ukrainian Post-Communist Transformation: Causes, Consequences and Threats - Kuczabski, Aleksander; Michalski, Tomasz (Quaestiones Geographicae, 2014)
The post-communist transformation of Ukraine differs significantly from that of other countries of Central and Eastern Europe. First of all, Ukraine’s transition from totalitarianism to democracy has been long and still remains uncompleted. The process of the democratic transformation in Ukraine is non-linear and can be described by frequent changes in transformation phases. The ultimate result of the country’s transformation determines to a considerable extent the geopolitical stability in entire Central and Eastern Europe.